What was washed away and what remained: an assessment of the impact of Hurricane Katrina on index crimes - Barton, Michael S. (Journal of crime and justice, 2020)
A substantial body of research has found crime was lower in areas characterized by a stronger community, but research on the importance of community for post-disaster levels of crime suggests a more nuanced relationship. While much of the research on disasters and crime emphasized the importance of collective resources, few studies explicitly assessed the importance of collective resources for crime during the recovery period. Further, recent research suggests crime-specific trends are differentially influenced by disasters. The current study contributes to research on the importance of community for post-disaster crime by examining the association of several forms of collective resources with six Part-1 crimes in New Orleans before, shortly after, and five years following Hurricane Katrina. Our results suggest the relationship of the community with crime is more nuanced than is often tested. We also found the association of neighborhood crime with forms of collective resources varied by crime type and temporally in ways that support some, but not other, existing theories on crime and disasters.